Korporativno upravljanje v javnem sektorju v Republiki Sloveniji - Bohinc, Rado (Podjetje in delo, 2016)
Public sector in Slovenia has been, from the point of view of property rights, organization and governance, the same since in the year 1991, when the Law on public institutions passed in the Slovene Parliament, as one of the important reform laws. At that time, the property of ex self-management communities was "temporarily" nationalized (transferred to state and municipal ownership). Notwithstanding huge reforms in the private business sector, the public sector remains as it was when it was taken by the state (nationalized). A reform is needed in this field and the article shows the weak points of the existing approaches in corporate governance in the public sector and presents the standpoints and guidelines for a corporate governance reform in public sector.
Keywords: javni sektor; javni zavodi; korporativno upravljanje; pravne osebe; upravljanje; vodenje